Five Postmortem Case Reports with Qualitative Analysis of Cyclopropylfentanyl by LC–MS-MS. Issue 4 (22nd November 2018) - Fagiola, Michael; Hahn, Timothy; Avella, Joseph
Abstract: In January 2018, the Drug Enforcement Agency temporarily designated cyclopropylfentanyl as a Schedule I drug. Over the course of 5 months (December 2017–May 2018), the Nassau County Medical Examiner Toxicology Laboratory qualitatively identified and confirmed cyclopropylfentanyl in specimens obtained from five postmortem cases. We describe the five cases and include pertinent autopsy findings and decedent histories, along with results for cyclopropylfentanyl determined in postmortem cardiac blood. Samples were prepared by an alkaline liquid–liquid extraction, with sample pH adjusted to >9 and utilizing an extraction solvent consisting of 90:10 hexane:ethyl acetate. Instrumental analysis was achieved via liquid chromatography tandem mass spectrometry with a dual jetstream electrospray source operating in positive ion mode. Two ion transitions were monitored for each analyte of interest and the internal standard. The estimated concentration range of cyclopropylfentanyl in the reported cases was 5.6 to 82 ng/mL for five postmortem cardiac blood specimens. All five cases included cyclopropylfentanyl in the established cause of death.